Entre estatais e transnacionais, "quantos ais": efeitos espaciais dos megaprojetos de mineração do carvão em Moatize, Moçambique - Bata, Eduardo Jaime (2018)
In Moatize, extraction of coal is an ancient activity, dating back to the early 19th century. Its development occurred concomitant consolidation of Moatize, primarily focus on coal mining in Mozambique. In fact, the coal basin of Moatize is the subject of research and mineral exploration, since the period of effective occupation. With independence and the process of building the State, mostly from the early 1990, the mining goes on to be one of the key sectors for the development of the country; Hence, all the conditions have been created for its growth. The new phase of coal extraction process that accompanied the changes underway in the world, especially since the 1970, have repercussions on the social structure, since the insertion of the capital involved arrangements of all kinds. In Moatize, the implementation of megaprojects demanded the space refunctionalization to meet the demands of the productive capital, a process that culminated with the compulsory displacement of the population. In this context, the research sought to understand the spatial effects of megaprojects of coal extraction in Moatize, from its contradictions, regarding the forms of spatial organization, in order to meet its needs. The proposition of this thesis is that there is a new geopolitical strategy that seeks to shift production, concentrated in Europe to New Territories, rich in natural resources, with tax incentives, weak labor and environmental legislation on the rights humans. This process strengthens the productive restructuring of capital and is characterized by the performance of large transnational corporations. Internally, this process relies on the actions of the State, creating the (legal, institutional and ideological) conditions to check rationality and visibility to megaprojects. So, considering the space as a system of systems and dialectical and historical materialism, as a method of research and interpretation of the phenomena; the qualitative research, secondary data collection, as well as field research, enabled the understanding of current arrangements in Moatize, as well as its effects on the spatial structure. With the implementation of megaprojects in Moatize, in addition to the pressure on State institutions to organize themselves, on the basis of these, there were also environmental degradation and, especially, the social disorganization – as a result of compulsory displacement and destruction of livelihoods. Thereby, the curtailment of collective goods, the difficulties of regular access to food in the resettlement, particularly, in Mwaladzi, the lack of land for production, lack of work, as well as the increased morbidity and mortality, are aspects that lead to the impoverishment of the resettled and exacerbate socio-environmental conflicts. In the meantime, the integration of megaprojects generated insignificant advantages for the local communities; However, this integration created and/or strengthened a small bourgeoisie connected to national political power – the capital partners.